Women in detective prose by Arthur Conan Doyle - Hodovalová, Lucie (Univerzita Pardubice, 2021)
The master's thesis focuses on the female characters appearing in the detective prose written by Arthur Conan Doyle. The theoretical part of the thesis provides information relevant to the cultural and historical characteristics of Scottish nationality and Scottish identity, description of female roles in Scotland and England during the 19th century, and characterisation of the detective genre. Relevant information about the life of the author is also provided in each chapter. The practical part is divided into eight chapters - each focusing on one story and its female characters. With the use of comparative analysis, the author tries to determine which of the three previously mentioned factors affected the characters in question the most and whether there is a connection between the characters and Scottish womanhood. The conclusion shows how Arthur Conan Doyle's writing was affected by all three aforementioned factors.
Ženy v detektivní próze Arthura Conana Doyla
Keywords: Doyle, Arthur Conan; viktoriánská Anglie; Skotská identita; feminismus; detektivní žánr; Doyle, Arthur Conan; Victorian England; Scottish identity; feminism; detective genre